Propagação in vitro de Andiroba (Carapa guianensis Aublet) - Brandao, Helio Leonardo Moura (2005)
The goal of this work was to develop a protocol for cloning through somatic embryogenesis of Andiroba (Carapa guianensis Aublet). A species abundantly found in north Brazil utilized for medicinal and cosmethic purposes and as a source of compounds that may be used to develop new synthetic drugs. To promote somatic embryogenesis were tested NAA, BAP, 2.4-D, TDZ and IBA, in different concentrations and different combinations in explants obteined of young plants trated with Benolmyl. The explants were cultivated in a medium containing MS salt and vitamins (Murashige & Skoog, 1962) being the mineral salts reduced to half strength and added with myo-inositol (100 mg.L-1), sucrose (30 g.L-1) and agar (8.0 g.L-1), and the pH was adjusted to 5.8. The cultures were inoculated and then kept at a 16 hour-photoperiod, temperature of 25 ± 2ºC and 25µmoles.m-2.s-1 radiation for 30 days. Three different sources of explant were tested: apical, leaf buds and leaves. The source that showed best resoults of rooting was the leaf buds trested with NAA 10,0 mgł. As well, leaves rooting showed best resoults treted with NAA. However apical source showed high level contamination, fact that took the increasing of a new protocol of assepsy. The results showed that it is possible to obtain high quantities of shoots and then plantlets which could be cultivated in vitro through the methods tested in this experiment. Apical source appear as the best way to obtain a plant of Andiroba by somathic embriogenesis, NAA promotes the rooting in leaf buds a leaves and BAP promotes shoots in apical explants. Key words: 1.Micropropagation, 2.Andiroba, 3.Hormonal combination and 4. growth regulators